THU0389 A Multiple Dose Study of AMG 811 (Anti-IFN-Gamma) in Subjects with Systemic Lupus Erythematosus and Active Nephritis. (9th June 2015) - Martin, D.A.; Amoura, Z.; Romero-Diaz, J.; Chong, Y.B.; Sanchez-Guerrero, J.; Chan, T.; Arnold, G.E.; Damore, M.A.; Sohn, W.; Chirmule, N.; Chiu, K.; Wang, C.; et al.
Abstract : Background: Interferon-gamma (IFN-g) is a pro-inflammatory cytokine that modulates the function of several important immune populations. Evidence from human and animal models suggests that increased levels of Type I and/or Type II IFN are associated with SLE. Objectives: This study assessed the safety, tolerability, PK and pharmacodynamic (PD) data from AMG 811, an anti-IFNg mAb, in subjects with active class III or IV LN. Methods: Subjects were enrolled if they had new onset or reactivation of biopsy-proven (within 18 months) class III or IV LN, UP/Cr >1 or 24 hr urine protein >1 g after at least 12 wks of treatment with MMF or AZA. Superimposed membranous changes were allowed. Subjects with rapidly progressive GN or significant chronicity were excluded. Subjects could receive oral prednisone at doses up to 20 mg/day. Subjects were randomized to placebo or ascending doses of AMG 811 (20, 60 or 120 mg given SC q4 wks for three doses at 3:1 allocation) in addition to MMF or AZA. The primary endpoints were safety, tolerability, and anti-drug antibodies. Serum AMG 811 concentrations, anti-AMG 811 antibodies and PD biomarkers (blood RNA and serum) were also assessed. Disease related assessments included reduction from baseline in proteinuria (24 hr urine and spot UP/Cr), SLEDAI scores and changes in SLE-related biomarkers. Results: 28 subjects were enrolled: 7 in the PBO group and 21 in the AMG 811 treatment groups. The proportion of subjects reporting treatment emergent AEs, including serious AEs, was similar between PBO and AMG 811 groups although a numerically higher proportion of subjects treated with AMG 811 had infectious events. AMG 811 displayed linear PK with half-life of 11-21 days. Exposures after doses of 20 & 60 mg in LN subjects were similar to exposures in non-renal SLE subjects. Antibodies to AMG 811 were not observed at any time. Baseline serum CXCL10 (IP-10) levels and IFNgamma-modulated mRNAs were higher in LN compared to non-renal SLE; both populations had elevated levels compared to healthy controls. AMG 811 (60 & 120 mg cohorts) led to a reduction in these biomarkers, albeit incomplete and transient, suggesting that AMG 811 may have had reduced target coverage in LN relative to non-renal SLE, where levels were reduced into the healthy range. Although numerous subjects demonstrated improvement in proteinuria, no consistent differences between AMG 811 treatment cohorts and PBO were discernable at week 12 in renal outcome or SLE-related serum biomarkers. Conclusions: AMG 811 demonstrated a favorable PK and immunogenicity profile in active LN subjects, and the overall safety profile was acceptable in this small study. Inhibition of pharmacodynamic biomarkers with doses up to 120 mg of AMG 811 appeared incomplete in LN subjects. There were no discernible effects of AMG 811 on clinical or SLE-related serologic outcome measures over the treatment period although interpretation is challenging given the small sample size. Disclosure of Interest: D. Martin Employee of: Amgen, Z. Amoura: None declared, J. Romero-Diaz: None declared, Y. Chong: None declared, J. Sanchez-Guerrero: None declared, T. Chan: None declared, G. Arnold Employee of: Amgen, M. Damore Employee of: Amgen, W. Sohn Employee of: Amgen, N. Chirmule Employee of: Amgen, K. Chiu Employee of: Amgen, C. Wang Employee of: Amgen, M. Boedigheimer Employee of: Amgen, B. Sullivan Employee of: Amgen, A. Welcher Employee of: Amgen, B. Kotzin Employee of: Amgen, J. Chung Employee of: Amgen